Electromyographic evaluation of the effectiveness of electrical stimulation of the pelvic floor muscles in a patient after total hysterectomy - Gabriela Kołodyńska; Adrian Sieroń (Kazimierz Wielki University, 2018)
Introduction. Total hysterectomy surgery is one of the most difficult operations in gynecological surgery. It involves removal of the stem and neck cancer. Often removed during surgery are also the ovaries and fallopian tubes. Indication for radical include histerektomiii cervical carcinoma, and adenocarcinoma of the endometrium. Performing this procedure it is always associated with the cessation of menstruation due to lack of the endometrium, which is located in the body of the uterus, in the case of simultaneous removal of the ovaries is created surgically induced menopause status. Endocrine disorders cause a lot of changes in the female body. One consequence may be the occurrence of the phenomenon of stress urinary incontinence. Objective of the work. The aim of this study was to evaluate the conduct of conservative patient suffering from stress urinary incontinence after total hysterectomy. Material and methods. The study involved a 60-year old female patient after a total hysterectomy with the removal of the fallopian tubes and ovaries in a problem that stress urinary incontinence. Before joining the project the patient was subjected to hormonal therapy and applied the pessary coil, which proved ineffective. For objective evaluation of resting bioelectric activity of the pelvic floor muscles used electromyograph Noraxon four-vaginal probe. Furthermore, in order to determine the degree of incontinence questionnaire was used Gaudenz and an analysis of voiding diary. All measurement methods have been made immediately before and after the therapy. The patient was subjected to combination therapy, which included electrical stimulation of the pelvic floor muscle exercises and biofeedback. Results. After therapy showed an increase in resting bioelectric activity of the pelvic floor muscles. In addition, the patient reported a reduction in symptoms. Conclusions. Electrical stimulation of the pelvic floor muscle exercises with biofeedback appears to be an effective treatment for urinary incontinence in women after total hysterectomy. Therefore, it seems necessary to continue research and to conduct them on a larger number of patients.